Endometrial markers of polycystic ovary syndrome (literature review) - E. M. Sharifulin; M. A. Sharifulin; L. V. Suturina (Acta Biomedica Scientifica, 2017)
Polycystic ovary syndrome (PCOS) is the most common endocrine disease in women and has a significant impact on various aspects of their health and the quality of life. The epidemiology of PCOS is well understood, while the prevalence of this syndrome depends on diagnostic criteria used, the characteristics of the population sample, and vary from 6-10 % to 15 % and higher. A number of studies suggest that the endometrium in women with PCOS differs from the normal endometrium morphologically and functionally. PCOS is associated with infertility problems, higher incidence of pregnancy complications and with increased risk of endometrial cancer, especially when obesity is present. The purpose of this review was to systematize the available data on molecular markers of endometrial pathology associated with PCOS. The information search was conducted using Internet resources (PubMed, EMBASE); literature sources for the period 1992-2016 were analyzed. Although the available information on the pathology of the endometrium is inconsistent, as a result of the analysis of published data, several mechanisms of endometrial disorders characteristic of PCOS have been identified: changes of hormonal effects (changes in hormone receptor expression, HOXA gene expression, changes in the synthesis of sex hormone binding globulin, enzymes involved in the metabolism of sex hormones in situ in the endometrium), hyperinsulinemia and disturbance of the glucose transport system, ratio of proinflammatory and antiinflammatory factors. Authors conclude that the majority of analyzed studies report an increased prevalence of histologically confirmed hyperplasia or endometrial cancer in women with PCOS. However, there are no clinical guidelines and approaches to prognosis of endometrial changes women with PCOS. It is still unclear if endometrial biopsy is necessary for all women with PCOS. The clinical significance of endometrial markers requires further investigation.